Pemetaan Penelitian Berorientasi Green Rantai Pasokan untuk Green Pemasaran : Analisis Bibliometrik: A Bibliometric Analysis - Nur Siswanto, Budi; Satiadharma, Moehamad; Arfiansyah, Ferry (Income Journal: Accounting, Management and Economic Research, 2023)
The purpose of this research is to undertake a bibliometric analysis of both the published literature on the green supply chain in the context of green marketing that was produced between 2013 and 2023. This study utilizes scientific mapping and analysis of publication performance to characterize the structure of green marketing publications as well as the patterns that have emerged within the field. The purpose of this research is to determine the contributions made by authors, journals, topic areas, the incidence of keywords, and trends in papers that have been published. The findings indicate that considerable growth occurred in the 2010s, despite the fact that the initial year of publishing did not see a significant amount of expansion. The findings of this investigation on the pattern of publications relating to environmentally responsible marketing reveal an average annual rise of 23 new publications in this field. Seven hundred and nine papers utilize the term "sustainability," making it the most popular choice. The interconnections between keywords provide information about the connections that often exist between terms that are used in a particular investigation. The visualization of research trends is offered in order to provide up-to-date reference information for academics. This reveals crucial research gaps as well as possible research pathways that may be pursued in the future in order to progress the consolidation of disciplines.